Fibrinolysis in Patients with Liver Disease - von Meijenfeldt, Fien A.; Lisman, Ton (Seminars in Thrombosis and Hemostasis, 2021)
Patients with liver disease acquire complex changes in their hemostatic system. Historically, these patients were considered to have a bleeding tendency related, in part, to a hyperfibrinolytic state. However, studies using more modern fibrinolysis tests have questioned the presence of a hyperfibrinolytic state in patients with liver disease and its association with bleeding risk. It may be that the sickest patients with liver disease do have fibrinolytic abnormalities. However, the debate on the fibrinolytic state of patients with (decompensated) cirrhosis or critically ill liver disease is complicated by the fact that hypo- and hyperfibrinolysis have been poorly defined. This could, in part, be explained by the lack of reliable tests that assess a patient's fibrinolytic status. Moreover, large clinical studies on the relationship between bleeding and fibrinolysis in patients with liver disease are scarce. Here, we provide an overview of the current knowledge on fibrinolysis in various types of liver diseases and possible implications as a target for therapeutic strategies in liver disease. As antifibrinolytic therapy has been shown to be safe and effective during liver transplantation, it could potentially be of use in patients with (either laboratory-established or suspected) hyperfibrinolysis-related bleeding.
Keywords: liver disease; coagulation; fibrinolysis; cirrhosis; acute liver failure; acute-on-chronic liver failure; antifibrinolytic therapy; liver transplantation